Phytochemical analysis of canola (Brassica napus L.) Cultivars: Mitigating lead stress effects through the foliar spray of potassium chloride - Ahmad, Aqsa; Saima, Shahzadi; Akmal, Farah; Yasin, Ghulam; ul Haq, Ikram; Altaf, Adeela (Emirates Journal of Food and Agriculture, 2023)
In the Botanical Garden and Research Laboratory of the Institute of Pure and Applied Biology, Bahauddin Zakariya University, Multan (Pakistan) the current work was performed to examine the effect of the foliar spray of potassium for lessening the toxicity of heavy metal in three varieties of Canola (Brassica napus L.) viz; Exceed, Cyclone and Legend. Seeds were grown in pots. They were arranged in a Completely Randomized Design (CRD). When seeds germinated, some were kept without treatment (control) and others were treated with 15mg/kg and 30mg/kg of Lead along with a Potassium spray. Plants were harvested and subjected to phytochemical studies. The role of phytochemical studies (alkaloid, flavonoid, and phenolic) showed an increase in response against heavy metal stress. While the plants treated with Potassium revealed a decreased response in phytochemical studies. Plants treated with both Pb metal and K expressed a lesser increase in phytochemical compared to plants only treated with metal. This study sheds light on the effectiveness of Potassium in improving growth and dealing with metal stress to decrease the harmful effect of heavy metals. However, further studies are required to identify the mechanisms of Potassium mediated alleviation of toxicity of Pb and other heavy metals. Keywords: Alkaloid; Canola; Lead; Potassium; Phytochemicals